Total Mobilization as a Total Defense Strategy Against Pandemics within the National Health System - Hadi Wichakso, Chahyo; Priyanto; Sulistyanto; Sofyan Hasdam, Andi (International Journal of Technology and Education Research, 2025)
The COVID-19 pandemic exposed significant vulnerabilities in Indonesia’s national health system, which was largely sectoral and insufficiently prepared for multidimensional crises. This study explores the implementation of total mobilization as a strategy of total war in managing the pandemic. Using a descriptive qualitative method through document analysis and comparative study, it examines cross-sectoral integration involving military deployment under Military Operations Other Than War (MOOTW), transformation of domestic health-related industries, and civil society engagement through ad-hoc institutions such as the COVID-19 Handling and National Economic Recovery Committee (KPCPEN). Findings indicate that total mobilization enabled a more effective crisis response through centralized coordination, logistical acceleration, and institutional synergy. Comparative insights from South Korea and Israel emphasize the importance of systemic preparedness, data-driven decision-making, and strong public trust. However, challenges include civic resistance, regional disparities, and the risk of human rights infringements. This study concludes by recommending a redesign of Indonesia’s national health resilience framework and the establishment of a permanent National Health Resilience Command to ensure long-term crisis readiness.